Molded body, precursor thereof, manufacturing method and use

By applying active energy to a resin-dielectric filler mixture, the method addresses the challenges of manufacturing dielectric composite materials with high dielectric constants and mechanical properties, resulting in flexible, durable film-like articles with controlled filler agglomerations.

JP7628510B2Active Publication Date: 2025-02-10DAICEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021574595
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-30
Filing Date
2021-01-12
Publication Date
2025-02-10
Estimated Expiration
2041-01-12

AI Technical Summary

Technical Problem

Existing dielectric composite materials face challenges in controlling the structure, manufacturing complexity, and achieving high dielectric constants while maintaining mechanical properties such as flexibility and durability, particularly in the context of miniaturized electronic components.

Method used

A method involving the application of active energy to a liquid precursor containing resin and dielectric filler to form agglomerated regions, allowing for the creation of molded bodies with cohesive dielectric filler portions and non-cohesive regions, utilizing photocurable resins and dielectric fillers like titanium-containing composite metal oxides to achieve high dielectric constants and mechanical properties.

Benefits of technology

The method enables the efficient manufacturing of film-like molded articles with high dielectric constants, low dielectric loss, and heat resistance, while maintaining flexibility and toughness, by forming dielectric filler agglomerations in specific patterns or shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628510000007
    Figure 0007628510000007
  • Figure 0007628510000008
    Figure 0007628510000008
  • Figure 0007628510000009
    Figure 0007628510000009
Patent Text Reader

Abstract

This molded body comprising a resin and a dielectric filler is produced through an aggregation step in which active energy is applied to a partial region of a liquid precursor including a resin precursor and dielectric fillers, and the dielectric fillers are aggregated to thereby obtain a precursor molded body. This molded body has: an aggregated part which is a region where the dielectric fillers are aggregated; and a non-aggregated part which is a region other than the aggregated part. In addition, the abundance ratio of the dielectric fillers in the aggregated part gradually decreases towards an interface between the aggregated part and the non-aggregated part, at least in the vicinity of the interface. The resin may be a cured product of a photocurable resin. The photocurable resin may be a cationically polymerizable compound. The proportion of the dielectric fillers may be 0.1-100 parts by mass with respect to 100 parts by mass of the resin. The molded body may have a film shape.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a molded article having a region in which a dielectric filler is aggregated in a resin, as well as a precursor, a manufacturing method and uses thereof. [Background technology]

[0002] Dielectric materials have the property of storing electricity when a voltage is applied, which causes electric polarization. Therefore, they are widely used as passive element components such as capacitors, resistors, and inductors in electrical and electronic equipment. In addition, the dielectric materials used for these applications are usually in sheet form, and require mechanical strength and durability, and are often wound into a roll, so flexibility is also required. For this reason, composite dielectric materials containing dielectric fillers in resin have also been developed as dielectric materials. However, in composite dielectric materials, there is a trade-off between electrical properties and mechanical properties, and if the ratio of dielectric fillers is increased to improve the relative dielectric constant, the mechanical properties of the dielectric material decrease. In recent years, with the spread of mobile devices such as smartphones, electronic components have become denser and smaller, so composite dielectric materials are also required to achieve both improved relative dielectric constant (higher dielectric constant) and mechanical properties such as flexibility.

[0003] JP 2018-6052 A (Patent Document 1) discloses a dielectric composite material in which a coating made of a dielectric filler is formed around matrix particles made of a resin, and the dielectric filler forms a three-dimensional network.

[0004] Japanese Patent No. 6264897 (Patent Document 2) discloses a high dielectric constant film in which inorganic filler is dispersed in a non-uniform state in the resin, which is produced by mixing a molten resin with a dispersion of inorganic filler dispersed in a dispersion medium, and applying a coating material in which the inorganic filler has been dispersed in the resin by ultrasonic vibration. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-6052 A [Patent Document 2] Patent No. 6264897 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the dielectric composite materials and high dielectric constant films of Patent Documents 1 and 2 are not easy to control in structure, are low in simplicity and productivity, and do not sufficiently increase the dielectric constant. Patent Document 1 describes the parallel model shown in the schematic cross-sectional view of Figure 1 as an unrealistic model that is not easy to manufacture using a small amount of dielectric filler.

[0007] Therefore, an object of the present disclosure is to provide a method for easily producing a molded body having a region in which dielectric filler aggregates in a resin.

[0008] Another object of the present disclosure is to provide a molded article in which aggregation regions of a dielectric filler are formed in various shapes or patterns, as well as a precursor, a manufacturing method and uses thereof.

[0009] Still another object of the present disclosure is to provide a film-like molded article having a filler aggregation region that crosses or penetrates the thickness direction, as well as a precursor, a production method, and uses thereof.

[0010] Another object of the present disclosure is to provide a film-like molded article that can achieve both mechanical properties such as flexibility (or toughness) and high dielectric constant properties, as well as a precursor, a production method, and uses thereof.

[0011] Still another object of the present disclosure is to provide a film-like molded product capable of improving high dielectric constant characteristics, low dielectric loss, and heat resistance, as well as a precursor, a production method, and uses thereof. [Means for solving the problem]

[0012] As a result of further intensive research to achieve the above-mentioned object, the inventors discovered that by applying active energy to a portion of a liquid precursor containing a resin precursor and a dielectric filler, the dielectric filler can be aggregated in a specific region, and a molded body having a region in which the dielectric filler is aggregated in the resin can be easily produced, thereby completing the present invention.

[0013] That is, the molded body of the present disclosure includes a resin and a dielectric filler (or dielectric particles), and is formed of an aggregation portion, which is a region where the dielectric filler is aggregated, and a non-aggregation portion, which is a region other than the aggregation portion, and the presence ratio of the dielectric filler in the aggregation portion gradually decreases toward the interface at least in the vicinity of the interface with the non-aggregation portion. The resin may be a cured product of a photocurable resin. The photocurable resin may be a cationic polymerizable compound. The dielectric filler may be an inorganic filler formed of a titanium-containing composite metal oxide. The ratio of the dielectric filler may be 0.1 to 100 parts by mass with respect to 100 parts by mass of the resin. The molded body may be in the form of a film. The film-shaped molded body may be formed in such a manner that a plurality of aggregation portions form a pattern shape, and at least one of the plurality of aggregation portions extends in the thickness direction and penetrates. The molded body may be a dielectric film.

[0014] The present disclosure also includes a method for producing the molded body, which includes an aggregation step of providing active energy to a partial region of a liquid precursor containing a resin precursor and a dielectric filler to aggregate the dielectric filler and obtain a precursor molded body. This manufacturing method may include a polymerization completion step of providing active energy to an uncured region of the precursor molded body that has undergone the aggregation step to complete polymerization. In the manufacturing method, the liquid precursor may include a photoacid generator, and the active energy may be active light. The present disclosure also includes a molded body obtained by the manufacturing method.

[0015] The present disclosure also includes a liquid precursor for forming a molded body comprising a photocurable resin and a dielectric filler, the liquid precursor comprising a photocurable resin and a dielectric filler, the liquid precursor having an aggregated portion which is a region where the dielectric filler is aggregated, and a non-aggregated portion which is a region other than the aggregated portion.

[0016] The present disclosure also includes a bonded body in which the molded body is bonded to a base material made of resin, ceramic, or metal. This bonded body may be a capacitor. Effect of the Invention

[0017] In the present disclosure, active energy is applied to a part of the region of the liquid precursor containing the resin precursor and the dielectric filler, so that a molded body having a region where the dielectric filler is aggregated in the resin can be easily (efficiently) manufactured. In addition, by using a desired mold or patterned mask, a molded body in which the aggregation region of the dielectric filler is formed in various shapes or patterns can be easily or accurately manufactured. Furthermore, a film-shaped (or sheet-shaped) molded body having a filler aggregation region that is transverse or continuous in the thickness direction (a high dielectric constant structure in which the dielectric is continuous in the thickness direction, called a parallel connection model: for example, the structure shown in FIG. 1 described in Patent Document 1) can be easily manufactured. Therefore, the dielectric properties can be effectively expressed in the thickness direction of the film-shaped molded body. In addition, since the dielectric properties can be efficiently imparted even with a small amount of added dielectric filler, the mechanical properties such as flexibility (or toughness) of the film-shaped molded body and high dielectric constant properties can be compatible. Furthermore, a molded body with high dielectric constant properties, low dielectric loss, and excellent heat resistance can also be obtained. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view of a composite material which is described in Patent Document 1 as being difficult to manufacture. [Diagram 2] FIG. 2 is a schematic partial vertical sectional view of a sheet-like molding of the present invention shown for explaining non-uniformity of the dielectric filler concentration in an aggregation portion. [Diagram 3]FIG. 3 is a diagram showing the pattern shape of the photomask used in the examples. [Figure 4] FIG. 4 is a diagram showing another pattern shape of the photomask used in the examples. [Diagram 5] FIG. 5 is a CCD (charge-coupled device) photograph of the surface of the film obtained in Comparative Example 1 ((a) 100x, (b) 400x). [Figure 6] FIG. 6 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Comparative Example 2. [Figure 7] FIG. 7 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 1. [Figure 8] FIG. 8 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 2. [Figure 9] FIG. 9 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 3. [Figure 10] FIG. 10 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 4. [Figure 11] FIG. 11 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 5. [Figure 12] FIG. 12 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 6. [Figure 13] FIG. 13 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 7. [Figure 14] FIG. 14 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 8. [Figure 15] FIG. 15 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 9. [Figure 16] FIG. 16 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 10. [Figure 17] FIG. 17 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 11. [Figure 18] FIG. 18 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 12. [Figure 19] FIG. 19 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 13. [Figure 20] FIG. 20 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 14. [Figure 21] FIG. 21 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 15. [Figure 22] FIG. 22 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 16. [Figure 23] FIG. 23 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 17. [Figure 24] FIG. 24 is a CCD photograph ((a) 100x, (b) 400x) of the surface of the film obtained in Example 18. [Diagram 25] FIG. 25 is a CCD photograph (100x) of the surface of the film obtained in Comparative Example 4. [Figure 26] FIG. 26 is a CCD photograph (100x) of the surface of the film obtained in Example 19. [Figure 27] FIG. 27 is a CCD photograph (100x) of the surface of the film obtained in Example 20. [Figure 28] FIG. 28 is a CCD photograph (100x) of the surface of the film obtained in Example 21. [Figure 29] FIG. 29 is a CCD photograph (100x) of the surface of the film obtained in Comparative Example 5. [Diagram 30] FIG. 30 is a CCD photograph (100x) of the surface of the film obtained in Example 22. [Diagram 31]FIG. 31 is a CCD photograph (100x) of the surface of the film obtained in Example 23. [Diagram 32] FIG. 32 is a CCD photograph (100x) of the surface of the film obtained in Example 24. [Diagram 33] FIG. 33 is a CCD photograph (100x) of the surface of the film obtained in Comparative Example 6. [Diagram 34] FIG. 34 is a CCD photograph (100x) of the surface of the film obtained in Example 25. [Diagram 35] FIG. 35 is a CCD photograph (100x) of the surface of the film obtained in Example 26. [Diagram 36] FIG. 36 is a CCD photograph (100x) of the surface of the film obtained in Example 27. [Figure 37] FIG. 37 is a CCD photograph (100x) of the surface of the film obtained in Comparative Example 7. [Figure 38] FIG. 38 is a CCD photograph (100x) of the surface of the film obtained in Example 28. [Figure 39] FIG. 39 is a CCD photograph (100x) of the surface of the film obtained in Example 29. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] [Molded body] The molded body of the present disclosure is a molded body that contains a resin and a dielectric filler, and is formed of an aggregation portion, which is a region where the dielectric filler is aggregated, and a non-aggregation portion (or matrix portion), which is a region other than the aggregation portion. A molded body (composite molded body) having such a structure is obtained by going through an aggregation process in which active energy is applied to a portion of a liquid precursor containing a resin precursor and a dielectric filler to aggregate the dielectric filler. In the present disclosure, it can be assumed that in the aggregation process, the resin precursor is polymerized in the region where the active energy is applied, and the dielectric filler moves with the polymerization to form an aggregation portion. The dielectric filler can be moved to a region where the active energy is not applied, or to a region where the active energy is applied, depending on the combination of the formulation and the selection of the manufacturing conditions.

[0020] (resin) The resin may be any resin that can be polymerized by active energy, and the resin obtained by polymerization may be a thermoplastic resin. However, in terms of ease of agglomerating the dielectric filler, a cured product of a curable resin that can be cured by active energy is preferred.

[0021] Examples of the curable resin include cationic polymerizable compounds and / or radical polymerizable resins. Among these, cationic polymerizable compounds are preferred from the viewpoint of productivity and the like. Cationic polymerizable compounds can easily and accurately prepare a desired molded body, probably because the reaction speed of the cationic polymerizable compounds is suitable for the movement (aggregation) of the dielectric filler. In addition, cationic polymerization can be reacted in the presence of oxygen, such as in air, and further, it is easy to control the curability by utilizing a dark reaction (or post-polymerization), and therefore has excellent productivity.

[0022] The cationic polymerizable compound is not particularly limited as long as it has at least one cationic polymerizable group, and may be a monofunctional cationic polymerizable compound having one cationic polymerizable group, or may be a polyfunctional cationic polymerizable compound having two or more identical or different cationic polymerizable groups. From the viewpoint of curability and resin strength (or molded body strength such as hardness), polyfunctional cationic polymerizable compounds are usually used. In the case of a polyfunctional cationic polymerizable compound, the number of cationic polymerizable groups can be selected from the range of, for example, about 2 to 10, for example, 2 to 8 (for example, 2 to 6), preferably 2 to 4, more preferably 2 to 3, and particularly 2.

[0023] Examples of the cationically polymerizable group include an epoxy (oxirane ring)-containing group, an oxetane ring-containing group, and a vinyl ether group.

[0024] The epoxy-containing group may be any group having at least an oxirane ring skeleton, and examples thereof include an epoxy group (or an oxirane-2-yl group), a 2-methyloxirane-2-yl group, a glycidyl-containing group (e.g., a glycidyl group, a 2-methylglycidyl group, etc.), an alicyclic epoxy group (e.g., an epoxycycloalkyl group such as a 3,4-epoxycyclohexyl group, an alkyl-epoxycycloalkyl group such as a 3,4-epoxy-6-methylcyclohexyl group, etc.), and the like.

[0025] The oxetane ring-containing group may be any group having at least an oxetane ring skeleton, and examples thereof include C groups such as oxetanyl groups (e.g., 3-oxetanyl groups), alkyloxetanyl groups (e.g., 3-methyl-3-oxetanyl groups, 3-ethyl-3-oxetanyl groups, etc.). 1-4 alkyloxetanyl groups, etc.

[0026] These cationic polymerizable groups may be used alone or in combination of two or more. Among these cationic polymerizable groups, epoxy-containing groups such as glycidyl-containing groups and alicyclic epoxy groups are often used from the viewpoint of curability suitable for the aggregation of dielectric fillers and productivity.

[0027] Representative examples of the cationically polymerizable compound include an epoxy compound having an epoxy-containing group, an oxetane compound having an oxetane ring-containing group, a vinyl ether compound having a vinyl ether group, and a polyfunctional compound having two or more types of cationically polymerizable groups selected from an epoxy-containing group, an oxetane ring-containing group, and a vinyl ether group.

[0028] These cationic polymerizable compounds can be used alone or in combination of two or more. Among these cationic polymerizable compounds, compounds having at least one cationic polymerizable group selected from the epoxy-containing group and oxetane ring-containing group, such as epoxy compounds and oxetane compounds, are often used, and among them, compounds having at least epoxy groups are preferred, and epoxy compounds are more preferred from the viewpoint of curability suitable for the aggregation of dielectric fillers and productivity.

[0029] The epoxy compound may be a monofunctional epoxy compound having one epoxy-containing group as a cationic polymerizable group, or a polyfunctional epoxy compound having two or more epoxy-containing groups. These epoxy compounds may be used alone or in combination of two or more.

[0030] Examples of the monofunctional epoxy compound include a monofunctional glycidyl-type epoxy compound having a glycidyl group (or a 2-methylglycidyl group), and a monofunctional alicyclic epoxy compound having an alicyclic epoxy group. Examples of monofunctional glycidyl type epoxy compounds include alkyl glycidyl ethers such as butyl glycidyl ether, 2-ethylhexyl glycidyl ether, dodecyl glycidyl ether, and tridecyl glycidyl ether; aryl glycidyl ethers such as phenyl glycidyl ether and alkyl phenyl glycidyl ether (tolyl glycidyl ether, t-butylphenyl glycidyl ether, etc.); (poly)alkylene glycol monoglycidyl ethers such as ethylene glycol monoglycidyl ether, 1,4-butanediol monoglycidyl ether, and diethylene glycol monoglycidyl ether; 2,3-epoxy-1-propanol (or glycidol); glycidyl (meth)acrylate; glycidyloxyalkyl (meth)acrylates such as glycidyloxyethyl (meth)acrylate; glycidyloxy(poly)alkoxyalkyl (meth)acrylates such as 2-(2-glycidyloxyethoxy)ethyl (meth)acrylate; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0031] Examples of monofunctional alicyclic epoxy compounds include 1,2-epoxycyclohexane, substituted epoxycyclohexanes (e.g., 1,2-epoxy-4-hydroxymethylcyclohexane, 1,2-epoxy-4-vinylcyclohexane, 3,4-epoxy-cyclohexylmethyl(meth)acrylate, and allyl-3,4-epoxycyclohexanecarboxylate).

[0032] Examples of polyfunctional epoxy compounds include polyfunctional glycidyl-type epoxy compounds having a glycidyl group (and / or a 2-methylglycidyl group), polyfunctional alicyclic epoxy compounds having at least one alicyclic epoxy group, etc. In this specification and claims, an epoxy compound having both a glycidyl group and an alicyclic epoxy group is classified as an alicyclic epoxy compound.

[0033] Examples of polyfunctional glycidyl-type epoxy compounds include glycidyl ether-type epoxy compounds (or glycidyl ether-type epoxy resins), glycidyl ester-type epoxy compounds (or glycidyl ester-type epoxy resins), glycidyl amine-type epoxy compounds (or glycidyl amine-type epoxy resins), and heterocyclic glycidyl-type epoxy compounds.

[0034] Examples of the glycidyl ester type epoxy compound include diglycidyl phthalates such as diglycidyl phthalate, diglycidyl tetrahydrophthalate, and diglycidyl hexahydrophthalate; homo- or copolymers of glycidyl (meth)acrylate; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0035] Examples of the glycidylamine type epoxy compound include tetraglycidyldiamines such as tetraglycidyldiaminodiphenylmethane, tetraglycidylmetaxylylenediamine, and tetraglycidylbisaminomethylcyclohexane; glycidylanilines such as diglycidylaniline, diglycidyltoluidine, N,N-diglycidyl-2,4,6-tribromoaniline, triglycidyl-p-aminophenol, and triglycidyl-m-aminophenol; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0036] Examples of heterocyclic glycidyl-type epoxy compounds include isocyanurate-type epoxy compounds such as triglycidyl isocyanurate; hydantoin-type epoxy compounds such as diglycidylhydantoin; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0037] These polyfunctional glycidyl type epoxy compounds can be used alone or in combination of two or more. Among these, glycidyl ether type epoxy compounds are preferred from the viewpoints of curability suitable for aggregation of dielectric fillers, productivity, etc.

[0038] Representative examples of the glycidyl ether type epoxy compound include aromatic glycidyl ether type epoxy compounds, alicyclic glycidyl ether type epoxy compounds, and aliphatic glycidyl ether type epoxy compounds.

[0039] Examples of the aromatic glycidyl ether type epoxy compound include polyglycidyl ethers of aromatic polyols or their alkylene oxide adducts, such as bi- or bisphenol type epoxy compounds (e.g., diglycidyl ethers of conventional bisphenols such as bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol AD ​​type epoxy compounds, and bisphenol S type epoxy compounds, and diglycidyl ethers of biphenols such as p,p'-biphenol); novolac type epoxy resins (e.g., phenol novolac type epoxy resins, cresol novolac type epoxy resins); polyglycidyl ethers of polyhydroxyarenes [e.g., bis(glycidyloxy)benzene, bis(glycidyloxy)naphthalene, etc.]; tetrakisphenol type epoxy compounds [e.g., tetrakis(glycidyloxyphenyl)ethane, etc.]; and C of aromatic polyols corresponding to these compounds. 2-4 Polyglycidyl ethers of alkylene oxide adducts; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0040] Examples of the alicyclic glycidyl ether type epoxy compound include polyglycidyl ethers of alicyclic polyols or their alkylene oxide adducts, and hydrogenated products of the aromatic glycidyl ether compounds [e.g., hydrogenated bi- or bisphenol type epoxy compounds (diglycidyl ethers of hydrogenated conventional bisphenols such as hydrogenated bisphenol A type epoxy compounds, etc.); hydrogenated novolac type epoxy resins, etc.]; bis(glycidyloxy)cyclohexane and other bis(glycidyloxy)cyclohexanes; 5-10 Cycloalkanes; Bis(glycidyloxy) C such as diglycidyl ether of 1,4-cyclohexanedimethanol 1-4 Alkyl)C 5-10 Cycloalkanes; the C of the corresponding alicyclic polyols 2-4 Polyglycidyl ethers of alkylene oxide adducts; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0041] These glycidyl ether type epoxy compounds can be used alone or in combination of two or more. Among these, aliphatic glycidyl ether type epoxy compounds are preferred because they have low viscosity and easily promote aggregation of the dielectric filler.

[0042] Examples of the aliphatic glycidyl ether type epoxy compound include polyglycidyl ethers of aliphatic polyhydric alcohols (aliphatic polyols) or condensates (or oligomers) thereof. Examples of the aliphatic polyhydric alcohols for forming the aliphatic glycidyl ether type epoxy compound include aliphatic diols [e.g., linear or branched C glycerides such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,2-butanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,8-octanediol, and 1,10-decanediol]. 2-12alkanediols, etc.]; trivalent or higher aliphatic polyols [for example, polymethylolalkanes such as trimethylolpropane; sugar alcohols such as glycerin, pentaerythritol, sorbitol, mannitol, etc.; alkylene oxide adducts thereof, etc.]. The condensation product of an aliphatic polyhydric alcohol may be a compound in which these aliphatic polyhydric alcohols are condensed alone or in combination of two or more kinds.

[0043] Representative examples of the aliphatic glycidyl ether type epoxy compound include divalent glycidyl ether type compounds and trivalent or higher glycidyl ether type compounds. Examples of the divalent glycidyl ether type compound include (poly)alkylene glycol diglycidyl ether represented by the following formula (1); diglycidyl ethers of the above-mentioned trivalent or higher aliphatic polyols such as trimethylolpropane diglycidyl ether, glycerin diglycidyl ether, and pentaerythritol diglycidyl ether, or condensates containing the polyols.

[0044] [ka]

[0045] (In the formula, A 1 is a linear or branched alkylene group, m is an integer of 1 or more, R 1 each independently represents a hydrogen atom or a methyl group).

[0046] In the formula (1), A 1 Examples of the linear or branched alkylene group represented by the formula (I) include linear or branched C alkylene groups such as an ethylene group, a propylene group, a trimethylene group, a 1,2-butanediyl group, a tetramethylene group, a 2,2-dimethylpropane-1,3-diyl group (neopentylene group), a pentamethylene group, a hexamethylene group, an octamethylene group, and a decamethylene group. 2-12 Alkylene groups (e.g., linear or branched C 2-10 alkylene group), preferably linear or branched C 2-8Alkylene groups (e.g., linear or branched C 3-7 alkylene group), more preferably a linear or branched C group such as an ethylene group, a propylene group, a trimethylene group, a tetramethylene group, or a hexamethylene group. 2-7 Alkylene groups (e.g., linear or branched C such as tetramethylene groups) 2-6 Alkylene group, preferably linear or branched C 3-6 Alkylene groups, especially linear or branched C 4-6 alkylene groups).

[0047] The repeat number m may be an integer of 1 or more, and may be selected from integers of about 1 to 30 (e.g., 1 to 15), for example, 1 to 10 (e.g., 1 to 8), preferably 1 to 6 (e.g., 1 to 4), more preferably 1 to 3 (e.g., 1 or 2), and particularly 1. If m is too large, the viscosity of the liquid precursor may increase, and the controllability of the dielectric filler may decrease. Also, when m is 2 or more, a plurality of alkylene groups A 1 The types may be the same or different from each other.

[0048] R 1 R may be either a hydrogen atom or a methyl group, and is usually a hydrogen atom. 1 The types may be different from each other, but are usually the same.

[0049] Specific examples of the (poly)alkylene glycol diglycidyl ether represented by the formula (1) include linear or branched C alkylene glycol diglycidyl ethers such as ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,3-propanediol diglycidyl ether, 1,2-butanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,5-pentanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, 1,8-octanediol diglycidyl ether, and 1,10-decanediol diglycidyl ether. 2-12Alkylene glycol diglycidyl ether; (di to penta) linear or branched chain C such as diethylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, and triethylene glycol diglycidyl ether 2-12 alkylene glycol diglycidyl ether; and compounds in which the glycidyloxy group of these compounds is replaced with a 2-methylglycidyloxy group.

[0050] The (poly)alkylene glycol diglycidyl ether represented by the formula (1) may be used alone or in combination of two or more. Among these, alkylene glycol diglycidyl ethers in which m is 1 are preferred, and among these, linear or branched C alkylene glycol diglycidyl ethers such as ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether are particularly preferred. 2-8 Alkylene glycol diglycidyl ether (e.g., linear or branched C 3-7 Alkylene glycol diglycidyl ethers), in particular linear or branched C 2-6 Alkylene glycol diglycidyl ether (e.g., linear or branched C such as neopentyl glycol, 1,6-hexanediol diglycidyl ether, etc.) 4-6 Alkylene glycol-diglycidyl ether, preferably branched C such as neopentyl glycol 4-6 Alkylene glycol diglycidyl ethers and the like are preferred.

[0051] On the other hand, examples of the trivalent or higher glycidyl ether type compounds include (poly)trimethylolpropane tri- to pentaglycidyl ethers [for example, mono- to tri(trimethylolpropane) tri- to pentaglycidyl ethers such as trimethylolpropane triglycidyl ether, ditrimethylolpropane triglycidyl ether, ditrimethylolpropane tetraglycidyl ether, etc.]; (poly)glycerin polyglycidyl ethers [for example, glycerin triglycidyl ether, di ... trivalent or higher polyols or condensates thereof (or their C) such as mono- to tri(glycerin) tri- to pentaglycidyl ethers, such as glycerin tetraglycidyl ether; (poly)pentaerythritol polyglycidyl ethers [for example, mono- to tri(pentaerythritol) tri- to octaglycidyl ethers, such as pentaerythritol triglycidyl ether, pentaerythritol tetraglycidyl ether, dipentaerythritol pentaglycidyl ether, dipentaerythritol hexaglycidyl ether, etc.]; 2-4 polyglycidyl ethers of alkylene oxide adducts; and compounds in which the glycidyl group in these compounds is replaced with a 2-methylglycidyl group.

[0052] These aliphatic glycidyl ether type epoxy compounds can be used alone or in combination of two or more. Among these aliphatic glycidyl ether type epoxy compounds, divalent glycidyl ether type compounds, especially (poly)alkylene glycol diglycidyl ether (particularly alkylene glycol diglycidyl ether) represented by the above formula (1) is often used because it is easy to improve the controllability of the dielectric filler and is easy to procure.

[0053] The polyfunctional alicyclic epoxy compound may be a compound having two or more epoxy-containing groups, at least one of which is an alicyclic epoxy group. Representative examples include a compound having one alicyclic epoxy group and one or more non-alicyclic epoxy groups [e.g., a compound having one each of an alicyclic epoxy group and an ethylene oxide group, such as 1,2:8,9-diepoxylimonene (or 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo[4.1.0]heptane, ARKEMA's "LIMONENE DIOXIDE"); a compound having two alicyclic epoxy groups; a compound having three or more alicyclic epoxy groups, etc.

[0054] An example of a compound having two alicyclic epoxy groups is a compound represented by the following formula (2).

[0055] [ka]

[0056] (In the formula, X represents a single bond or a linking group, and the cyclohexene oxide groups may each have a substituent.)

[0057] In formula (2), examples of the linking group represented by X include a divalent hydrocarbon group, an alkenylene group in which some or all of the carbon-carbon double bonds have been epoxidized, a carbonyl group (-CO-), an ether bond (-O-), an ester bond (-COO-), a carbonate group (-O-CO-O-), an amide group (-CONH-), and groups in which a plurality of these are linked together.

[0058] The divalent hydrocarbon group is, for example, a linear or branched C 1-18 Alkylene group, divalent C 3-18 Alicyclic hydrocarbon groups, etc. Linear or branched chain C 1-18 Examples of the alkylene group include a methylene group, a methylmethylene group, a dimethylmethylene group, an ethylene group, a propylene group, and a trimethylene group. 3-18Examples of the alicyclic hydrocarbon group include cycloalkylene groups (including cycloalkylidene groups) such as a 1,2-cyclopentylene group, a 1,3-cyclopentylene group, a cyclopentylidene group, a 1,2-cyclohexylene group, a 1,3-cyclohexylene group, a 1,4-cyclohexylene group, and a cyclohexylidene group.

[0059] Examples of the alkenylene group in the alkenylene group in which a part or all of the carbon-carbon double bonds are epoxidized (sometimes referred to as an "epoxidized alkenylene group") include linear or branched C alkylene groups such as vinylene, propenylene, 1-butenylene, 2-butenylene, butadienylene, pentenylene, hexenylene, heptenylene, and octenylene. 2-8 In particular, the epoxidized alkenylene group is preferably an alkenylene group in which all of the carbon-carbon double bonds are epoxidized, and more preferably a C 2-4 It is an alkenylene group.

[0060] Of these, X is preferably a carbonyloxymethylene group.

[0061] In the above formula (2), the two cyclohexene oxide groups may each independently have a substituent bonded thereto. Examples of the substituent include a halogen atom, C 1-10 Alkyl group, C 1-10 Alkoxy group, C 2-10 Alkenyloxy group, C 6-14 Aryloxy group, C 7-18 Aralkyloxy group, C 1-10 Acyloxy group, C 1-10 Alkoxycarbonyl group, C 6-14 Aryloxycarbonyl group, C 7-18 Aralkyloxycarbonyl group, epoxy group-containing group, oxetane ring-containing group, C 1-10 Examples of the substituent include an acyl group, an isocyanate group, a sulfo group, a carbamoyl group, an oxo group, etc. It is preferable that the cyclohexene oxide group is not bonded to any of the above substituents.

[0062] Representative examples of the compound represented by the above formula (2) include (3,4,3',4'-diepoxy)bicyclohexyl, bis(3,4-epoxycyclohexylmethyl)ether, 1,2-epoxy-1,2-bis(3,4-epoxycyclohexan-1-yl)ethane, 2,2-bis(3,4-epoxycyclohexan-1-yl)propane, 1,2-bis(3,4-epoxycyclohexan-1-yl)ethane, and compounds represented by the following formulas (2-1) to (2-8).

[0063] [ka]

[0064] (Wherein, L is C 1-8 Alkylene groups (e.g., linear or branched C such as methylene, ethylene, propylene, and isopropylene groups) 1-3 an alkylene group), and n1 and n2 each represent an integer of 1 to 30.

[0065] Examples of the compound having three or more alicyclic epoxy groups include compounds represented by the following formulas (2-9) and (2-10).

[0066] [ka]

[0067] (In the formula, n3 to n8 each independently represent an integer of 1 to 30).

[0068] These polyfunctional alicyclic epoxy compounds can be used alone or in combination of two or more. Among these polyfunctional alicyclic epoxy compounds, compounds having two alicyclic epoxy groups such as the compound represented by the formula (2) are preferred, and among them, 3,4-epoxycyclohexylmethyl(3,4-epoxy)cyclohexanecarboxylate (the compound represented by the formula (2-1)) in which X is a carbonyloxymethylene group is preferred.

[0069] Examples of polyfunctional epoxy compounds other than the polyfunctional glycidyl-type epoxy compounds and the polyfunctional alicyclic epoxy compounds include 1,2-epoxy-4-(2-oxiranyl)cyclohexane adducts of polyols (e.g., trimethylolpropane) (e.g., "EHPE3150" manufactured by Daicel Corporation).

[0070] These polyfunctional epoxy compounds can be used alone or in combination of two or more. Among these epoxy compounds, polyfunctional epoxy compounds are usually used from the viewpoint of curability and productivity. Among the polyfunctional epoxy compounds, polyfunctional glycidyl type epoxy compounds and polyfunctional alicyclic epoxy compounds are preferred from the viewpoint of curability and productivity that are particularly suitable for the aggregation of dielectric fillers, and more preferred are glycidyl ether type epoxy compounds and compounds having two alicyclic epoxy groups, and more preferred are (poly)alkylene glycol diglycidyl ether represented by the formula (1) and compounds having two alicyclic epoxy groups represented by the formula (2).

[0071] Furthermore, in terms of excellent controllability of the dielectric filler and improved flexibility of the molded body, a combination of a polyfunctional alicyclic epoxy compound and a polyfunctional glycidyl-type epoxy compound is preferred, and a combination of a compound having two alicyclic epoxy groups represented by the formula (2) and a (poly)alkylene glycol diglycidyl ether represented by the formula (1) is particularly preferred.

[0072] The mass ratio of the polyfunctional alicyclic epoxy compound to the polyfunctional glycidyl-type epoxy compound (former / latter) can be selected within the range of 99 / 1 to 1 / 99, and is, for example, 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80, further preferably 70 / 30 to 30 / 70, and further preferably 60 / 40 to 40 / 60.

[0073] From the viewpoint of promoting the aggregation of the dielectric filler in the aggregation step, the viscosity of the cationic polymerizable compound at 25°C can be selected from a range of, for example, about 500 mPa·s or less (for example, 1 to 400 mPa·s), for example, 2 to 350 mPa·s (for example, 3 to 300 mPa·s), preferably 4 to 250 mPa·s (for example, 5 to 200 mPa·s), more preferably 5 to 150 mPa·s (for example, 5 to 100 mPa·s), and even more preferably 5 to 80 mPa·s (for example, 5.5 to 50 mPa·s), and among these, preferably 6 to 30 mPa·s (for example, 6.5 to 20 mPa·s), and even more preferably 7 to 15 mPa·s (for example, 7.5 to 10 mPa·s). The viscosity can be measured using a conventional viscometer (for example, a single cylindrical rotational viscometer, etc.).

[0074] The proportion of the cationic polymerizable compound can be selected from the range of, for example, about 10 to 100 mass% (e.g., 30 to 99 mass%) relative to the total resin contained in the liquid precursor, and may be, for example, about 50 to 100 mass% (e.g., 60 to 98 mass%), preferably 70 to 100 mass% (e.g., 80 to 97 mass%), more preferably 80 to 100 mass% (e.g., 90 to 95 mass%), and particularly 95 to 100 mass% (particularly, substantially 100 mass%). If the proportion of the cationic polymerizable compound is too low, there is a risk that the aggregation portion cannot be formed easily or sufficiently (or accurately) in the aggregation step.

[0075] As the curable resin, a photocurable resin is preferred from the viewpoint of easiness in forming aggregated portions, and a photocationically polymerizable compound is particularly preferred.

[0076] (Polymerization initiator) The molded body (or the liquid precursor for forming the molded body) may further contain a polymerization initiator for polymerizing the resin. The polymerization initiator can be appropriately selected depending on the type of resin, and when the resin is a curable resin, it may be a radical polymerization initiator, a cationic polymerization initiator, or an anionic polymerization initiator. A preferred polymerization initiator is a cationic polymerization initiator (acid generator). Cationic polymerization initiators include photoacid generators and thermal acid generators.

[0077] Examples of photoacid generators include sulfonium salts (salts of sulfonium ions and anions), diazonium salts (salts of diazonium ions and anions), iodonium salts (salts of iodonium ions and anions), selenium salts (salts of selenium ions and anions), ammonium salts (salts of ammonium ions and anions), phosphonium salts (salts of phosphonium ions and anions), oxonium salts (salts of oxonium ions and anions), salts of transition metal complex ions and anions, and bromine compounds. These photoacid generators can be used alone or in combination of two or more. Among these photoacid generators, acid generators with high acidity, such as sulfonium salts, are preferred from the viewpoint of improving reactivity.

[0078] Examples of sulfonium salts include triphenylsulfonium salts, tri-p-tolylsulfonium salts, tri-o-tolylsulfonium salts, tris(4-methoxyphenyl)sulfonium salts, 1-naphthyldiphenylsulfonium salts, 2-naphthyldiphenylsulfonium salts, tris(4-fluorophenyl)sulfonium salts, tri-1-naphthylsulfonium salts, tri-2-naphthylsulfonium salts, tris(4-hydroxyphenyl)sulfonium salts, diphenyl[4-(phenylthio)phenyl]sulfonium salts, [4-(4-biphenylthio)phenyl]-4-biphenylphenylsulfonium salts, 4-(p-tolylthio)phenyl Examples of the sulfonium salts include triarylsulfonium salts such as aryldi-(p-phenyl)sulfonium salt; diarylsulfonium salts such as diphenylphenacylsulfonium salt, diphenyl4-nitrophenacylsulfonium salt, diphenylbenzylsulfonium salt, and diphenylmethylsulfonium salt; monoarylsulfonium salts such as phenylmethylbenzylsulfonium salt, 4-hydroxyphenylmethylbenzylsulfonium salt, and 4-methoxyphenylmethylbenzylsulfonium salt; and trialkylsulfonium salts such as dimethylphenacylsulfonium salt, phenacyltetrahydrothiophenium salt, and dimethylbenzylsulfonium salt. These sulfonium salts can be used alone or in combination of two or more. Among these sulfonium salts, triarylsulfonium salts are preferred.

[0079] Examples of anions (counter ions) that form salts with cations include SbF 6- , P.F. 6- , B.F. 4- , fluoroalkyl fluorophosphate ion [(CF 3 CF 2 ) 3 PF 3- , (CF 3 CF 2 CF 2 ) 3 PF 3- etc.], (C 6 F 5 ) 4 B - , (C 6 F5 ) 4 Ga - , sulfonate anions (trifluoromethanesulfonate anion, pentafluoroethanesulfonate anion, nonafluorobutanesulfonate anion, methanesulfonate anion, benzenesulfonate anion, p-toluenesulfonate anion, etc.), (CF 3 SO 2 ) 3 C - , (CF 3 SO 2 ) 2 N - , perhalogen acid ions, halogenated sulfonate ions, sulfate ions, carbonate ions, aluminate ions, hexafluorobismuthate ions, carboxylate ions, arylborate ions, thiocyanate ions, nitrate ions, etc. These anions can be used alone or in combination of two or more. Of these anions, SbF 6- , P.F. 6- , fluorinated alkyl fluorophosphate ions, etc. are commonly used, and from the standpoint of solubility, etc., fluorinated alkyl fluorophosphate ions, etc. are preferred. Usually, PF 6- It is often the case that:

[0080] The photoacid generator may be a commercially available photoacid generator. Examples of commercially available photoacid generators include "CPI-101A", "CPI-110A", "CPI-100P", "CPI-110P", "CPI-210S", and "CPI-200K" manufactured by San-Apro Co., Ltd.; "CYRACURE UVI-6990" and "CYRACURE UVI-6992" manufactured by Dow Chemical Co.; "UVACURE1590" manufactured by Daicel-Allnex Co., Ltd.; "CD-1010", "CD-1011", and "CD-1012" manufactured by Sartomer, USA; "Irgacure-264" manufactured by BASF; "CIT-1682" manufactured by Nippon Soda Co., Ltd.; and "PHOTOINITIATOR 2074" manufactured by Rhodia Japan Co., Ltd.

[0081] Examples of thermal acid generators include arylsulfonium salts, aryl iodonium salts, allene-ion complexes, quaternary ammonium salts, aluminum chelates, and boron trifluoride amine complexes. These thermal acid generators can be used alone or in combination of two or more. Among these thermal acid generators, acid generators with high acidity, such as arylsulfonium salts, are preferred in terms of improving reactivity. Examples of anions include the same anions as those of photoacid generators, such as SbF 6- The antimony fluoride ion may be an antimony fluoride ion such as

[0082] The thermal acid generator may be a commercially available one, such as "SAN-AID SI-60L", "SAN-AID SI-60S", "SAN-AID SI-80L", and "SAN-AID SI-100L" manufactured by Sanshin Chemical Industry Co., Ltd., or "SP-66" and "SP-77" manufactured by ADEKA Corporation.

[0083] These photo- or thermal acid generators may be capable of generating acid by the action of either light or heat.

[0084] These cationic polymerization initiators can be used alone or in combination of two or more. Among these cationic polymerization initiators, photoacid generators are preferred because they can easily form aggregated portions in a pattern using a photomask or the like.

[0085] The proportion of the polymerization initiator (particularly, the cationic polymerization initiator) may be appropriately selected according to the type of resin, etc., to adjust the curability of the liquid precursor, and may be selected from a range of about 0.01 to 100 parts by mass relative to 100 parts by mass of the total amount of the resin (particularly, the cationic polymerizable compound), for example, 0.1 to 50 parts by mass, preferably 1 to 30 parts by mass, more preferably 3 to 20 parts by mass, more preferably 5 to 15 parts by mass, and most preferably 8 to 12 parts by mass. If the proportion of the polymerization initiator is too small, the curing reaction is unlikely to proceed, and the dielectric filler is unlikely to aggregate in the aggregation step, and if it is too large, the curing reaction is too fast, and the dielectric filler is likely to be cured in a state where aggregation is insufficient in the aggregation step, and it is also costly and disadvantageous in terms of productivity.

[0086] (Dielectric filler) As the dielectric filler, a conventional dielectric filler (dielectric particles or granular dielectrics) can be used. Conventional dielectric fillers can be roughly classified into inorganic fillers (or particles) and organic fillers (or particles).

[0087] Materials for the inorganic filler include metal oxides and metal composite oxides. Examples of metal oxides include titanium oxide, zirconium oxide, and lanthanum oxide. Examples of composite metal oxides include magnesium titanate, calcium titanate, strontium titanate, and barium titanate (BaTiO 3 Metallic titanium oxides such as zinc titanate and bismuth titanate; metal zirconates such as barium zirconate; metal stannates such as barium stannate; metal hafnates such as barium hafnate; metal niobates such as lithium niobate; metal tantalates such as lithium tantalate; metal zirconates such as barium titanate and lead zirconate titanate (PZT). In addition, composite metal oxides such as barium titanate may further contain, as trace components, alkaline earth metals such as calcium and strontium, and rare earth metals such as yttrium, neodymium, samarium, and dysprosium.

[0088] Examples of materials for the organic filler include vinylidene fluoride polymers such as polyvinylidene fluoride, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, and vinylidene fluoride-vinylidene hexafluoride copolymer; odd-numbered polyamides (odd-numbered nylons) such as polyamide 5, polyamide 7, and polyamide 11; cyanoresins such as cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl hydroxyethyl cellulose, and cyanoethyl cellulose; polyurea; polythiourea; and triglycine sulfate.

[0089] The dielectric fillers formed of these materials can be used alone or in combination of two or more. Among these, inorganic fillers are preferred from the viewpoint of ease of forming aggregated parts, inorganic fillers formed of composite metal oxides (composite metal oxide fillers) are more preferred, inorganic fillers formed of titanium-containing composite metal oxides are even more preferred, and inorganic fillers formed of alkaline earth metal titanates are most preferred. In addition, the dielectric filler may be an inorganic filler having a perovskite structure (particularly, an inorganic filler formed of composite metal oxides having a perovskite structure) from the viewpoint of ease of forming aggregated parts. Furthermore, among the dielectric fillers, ferroelectric fillers may be used from the viewpoint of improving the relative dielectric constant of the molded body.

[0090] The dielectric constant of the dielectric filler (ε r ) may be 100 or more, for example, 500 or more, preferably 1000 or more, and more preferably 3000 or more (for example, 3000 to 10000).

[0091] The shape of the dielectric filler (shape of primary particles) is not particularly limited as long as it is granular, and examples include spherical shapes such as perfect spheres or approximately spherical shapes; ellipsoids (oval spheres); pyramidal shapes such as cones and polygonal pyramids; polygonal prisms such as cubes and rectangular prisms; plate shapes such as flat, scale, and thin flakes; rod shapes or bars; linear shapes such as fibers and needles; and irregular shapes.

[0092] The median particle size of the dielectric filler (D 50) may be 1 μm or more, but is preferably 1 μm or less, and more preferably 0.01 to 1 μm. If the central particle size is too small, the viscosity of the liquid precursor is likely to increase, making it difficult for the dielectric filler to aggregate in the aggregation step, and it may be difficult to effectively impart dielectric properties due to the influence of interface resistance (contact resistance). Conversely, if it is too large, the dielectric filler may be difficult to move in the aggregation step, making aggregation difficult, and depending on the dielectric filler, photocurability may be reduced due to the influence of the shadow of the dielectric filler itself. Also, in order to efficiently increase the dielectric filler concentration in the aggregation portion, particles of different sizes may be intentionally mixed in a predetermined ratio.

[0093] In this specification and claims, the median particle size of the dielectric filler means the median particle size of the primary particles, and can be measured on a volume basis using a nanoparticle size distribution measuring device ("SALD-7500nano" manufactured by Shimadzu Corporation). It can also be determined by image analysis. That is, for example, a scanning electron microscope (SEM) is used to take electron microscope images of a sufficient number of particulate matter (e.g., 10 or more), and the maximum diameter, intersection diameter, and thickness of these particulate matter are measured and then the average is calculated.

[0094] The ratio of the dielectric filler can be selected from the range of about 0.01 to 300 parts by mass (for example, 0.1 to 100 parts by mass) relative to 100 parts by mass of the resin (or resin precursor), and is, for example, 0.1 to 80 parts by mass, preferably 0.2 to 70 parts by mass. Even if the ratio of the dielectric filler is high, the aggregation of the dielectric filler can be controlled, and the ratio of the dielectric filler may be, for example, 1 to 300 parts by mass, preferably 10 to 200 parts by mass, more preferably 20 to 100 parts by mass, and more preferably 30 to 80 parts by mass relative to 100 parts by mass of the resin. If the ratio of the dielectric filler is too small, there is a risk that the relative dielectric constant of the molded body cannot be improved, but in the present disclosure, even with a relatively small amount of dielectric filler, the relative dielectric constant can be improved by forming an aggregation portion. On the other hand, if the amount is too large, there is a risk that the viscosity of the liquid precursor is easily increased, making it difficult for the dielectric filler to aggregate in the aggregation step, and depending on the dielectric filler, there is a risk that the photocurability is reduced due to the influence of the shadow of the dielectric filler itself. Furthermore, the flexibility (or toughness) of the resulting molded article is likely to decrease, resulting in a brittle molded article.

[0095] (Other ingredients) The molded body (or the liquid precursor for forming the molded body) may further contain other components such as conventional additives, in addition to the resin and the dielectric filler, as necessary.

[0096] Examples of conventional additives include stabilizers (heat stabilizers, ultraviolet absorbers, light stabilizers, antioxidants, etc.), dispersants, antistatic agents, colorants, lubricants, sensitizers (acridines, benzoflavins, perylenes, anthracenes, thioxanthones, laser dyes, etc.), sensitizing assistants, curing accelerators (imidazoles, alkali metal or alkaline earth metal alkoxides, phosphines, amide compounds, Lewis acid complex compounds, sulfur compounds, boron compounds, condensable organometallic compounds, etc.), antifoaming agents, and flame retardants. These additives can be used alone or in combination of two or more. The ratio of conventional additives may be, for example, 30 parts by mass or less (for example, 0.01 to 30 parts by mass), preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of the resin (or resin precursor).

[0097] (Characteristics of Molded Product) As described above, the aggregated portion of the molded body is a region formed by the application of activation energy, in which the dielectric filler is aggregated without being uniformly dispersed inside the molded body, but has a structure in which the presence ratio of the dielectric filler gradually decreases toward the interface at least near the interface with the non-aggregated portion (or matrix portion). That is, the aggregated portion does not have a homogeneous structure in which the dielectric filler is present at a constant ratio in the entire region of the aggregated portion, but has a concentration gradient or inclination structure in which the concentration gradually decreases (linearly or curvedly, or continuously or stepwise) at least near the interface between the aggregated portion and the non-aggregated portion. In particular, although the structure near the interface has a concentration gradient, it is not typical, so it is impossible or extremely difficult to specify the microscopic structure, and is not practical. In addition, by having this structural characteristic, it is possible to impart characteristics derived from the present disclosure, such as improvement of interface strength by anchor effect. Such a structure can be easily observed using a digital microscope (CCD observation image) or the like. For example, in a CCD photograph taken of the cross section or surface of the aggregation portion at a magnification of about 200 to 1000 times, it is easy to confirm that the presence ratio (concentration) of the dielectric filler in the aggregation portion is non-uniform.

[0098] The non-uniformity of the dielectric filler content (concentration) in the agglomeration can also be confirmed by detecting the elements (also called dielectric filler constituent elements) or chemical species constituting the dielectric filler through elemental analysis (or surface analysis) or chemical species analysis of a specific region in the agglomeration. The method (or device) for elemental analysis may be appropriately selected according to the form of the molded body (such as the type of dielectric filler), and examples of the method include conventional methods such as energy dispersive X-ray spectroscopy (EDX or EDS), wavelength dispersive X-ray spectroscopy (WDX, WDS or EPMA), X-ray photoelectron spectroscopy (XPS or ESCA), Auger electron spectroscopy (AES), and secondary ion mass spectrometry (SIMS) [such as time-of-flight secondary ion mass spectrometry (TOF-SIMS)]. Conventional methods such as Raman spectroscopy and infrared spectroscopy (IR) are used to detect chemical species, and energy dispersive X-ray spectroscopy such as SEM-EDX (SEM-EDS) is usually used.

[0099] In the molded body of the present disclosure, the dielectric filler concentration decreases or gradually decreases toward the interface (or interface direction) at least in the peripheral region near the interface of the aggregation portion, and therefore, when a specific region within the aggregation portion is subjected to elemental analysis, it can be confirmed that the presence ratio of the dielectric filler constituent elements at least in the peripheral region near the interface of the aggregation portion is low.

[0100] As a representative confirmation method, for example, first, in a molded body cross section (or surface) that crosses the center of the agglomeration part (the part inside the agglomeration part that is the farthest from the interface with the adjacent non-agglomeration part that divides the agglomeration part) and the interface between the agglomeration part and the adjacent non-agglomeration part along the thickness direction, the agglomeration part is divided into three equal parts from the center toward the interface (or interface direction) (divided into three parts so that the distance from the center to the interface is equal). The divided regions are defined as a central region (center, vicinity of the center, or first region), an intermediate region (intermediate region, intermediate region, or second region), and a peripheral region (peripheral region, vicinity of the interface, or third region) in the order from the center toward the interface. Each of these regions is subjected to elemental analysis to measure the abundance ratio of at least one element that constitutes the dielectric filler, and the abundance ratios of each region are compared, whereby it can be confirmed that the abundance ratio in the peripheral region is at least lower than the abundance ratio in the intermediate region. The abundance ratio may be a ratio based on the number of atoms (frequency or intensity), but is usually a ratio based on the mass of atoms. In the present specification and claims, a specific method for elemental analysis may be SEM-EDS (main body: Hitachi High-Technologies Corporation's "SU5000"; SDD detector: Oxford Instruments' "X-MaxN").

[0101] Hereinafter, a more specific description will be given based on Fig. 2. Fig. 2 is a schematic partial longitudinal sectional view of the molded body of the present disclosure, that is, a film (or sheet)-like molded body having an aggregation portion 1 in which a dielectric filler penetrates in the thickness direction. That is, Fig. 2 shows a cross section (or longitudinal section) passing through (or crossing) a center portion 4 (a central axis extending in the thickness direction at the center in the planar direction of the aggregation portion) of any aggregation portion 1 in the molded body, and an interface 3 between the aggregation portion 1 and a non-aggregation portion 2 adjacent thereto, and substantially parallel to the thickness direction of the molded body.

[0102] In the figure, within the aggregation part, the region from the central part 4 to at least one interface (the interface on the left side of the central part 4 in the figure) 3 (as close as possible) is divided into three in the width direction (horizontal direction) of the aggregation part so that the distance from the central part 4 to the interface 3 is equal. The divided regions are designated as a central region 1a, an intermediate region 1b, and a peripheral region (or near the interface) 1c in the order from the region on the central part 4 side toward the interface 3. In each of the regions 1a to 1c, elemental analysis is performed at a plurality of randomly selected measurement points (preferably three or more) to obtain the abundance ratio of at least one element among the dielectric filler constituent elements for each measurement point. The average value of the obtained abundance ratios is calculated and adopted as the abundance ratio of each of the regions to which the measurement points belong. By comparing the abundance ratios of the dielectric filler constituent elements in each of the regions obtained in this way, it can be confirmed that the abundance ratio (concentration) of the dielectric filler in the aggregation part is non-uniform.

[0103] More specifically, the distribution state of the dielectric filler in the agglomeration part of the cross section of the compact (longitudinal cross section passing through the center part and the interface of the agglomeration part) may be visualized by a graph in which the horizontal axis represents the horizontal direction in the cross section of the compact (direction perpendicular to the thickness direction, or the width direction of the agglomeration part) and the vertical axis represents the abundance ratio (dielectric filler concentration) of one element selected from the dielectric filler constituent elements. In the compact of the present disclosure, the abundance ratio (concentration) in the peripheral region is lower than the abundance ratio (concentration) in at least the intermediate region, possibly because the agglomeration part is formed by the movement of the dielectric filler. Therefore, the shape (concentration distribution of the aggregate part in the vertical cross section) shown by the graph (a graph with the horizontal axis being the section from one peripheral region through the central region (or center) to the other peripheral region) can be a mountain shape or a normal distribution shape [a shape in which the abundance ratio in the central region is high, and decreases linearly or curvedly and continuously or stepwise as it approaches the peripheral region (interface direction)]; a trapezoid shape [a shape in which the abundance ratios in the central region and intermediate region are almost equally high, and decrease linearly or curvedly and continuously or stepwise as it approaches the peripheral region]; a caldera shape [a shape in which the abundance ratio in the intermediate region is high, and decreases linearly or curvedly and continuously or stepwise as it approaches the central region and peripheral region], and usually, the shape is often a mountain shape. Note that the graph shape (concentration distribution) may be satisfied for at least one element of the dielectric filler constituent elements, and may be satisfied for preferably a plurality of dielectric filler constituent elements, and more preferably for all dielectric filler constituent elements (the same applies to the abundance ratio ratios described below).

[0104] The ratio of the abundance ratio in the peripheral region (third region) to the abundance ratio in the intermediate region (second region) can be selected, for example, from a range of about third region / second region (mass basis) = 1 / 1.01 to 1 / 20 (e.g., 1 / 1.05 to 1 / 15) and may be, for example, about 1 / 1.1 to 1 / 10 (e.g., 1 / 1.15 to 1 / 8), preferably about 1 / 1.2 to 1 / 7 (e.g., 1 / 1.25 to 1 / 6), and more preferably about 1 / 1.5 to 1 / 5 (e.g., 1 / 2 to 1 / 4, preferably 1 / 2.5 to 1 / 3.5).

[0105] The abundance ratio in the peripheral region (near the interface or in the third region) does not necessarily have to be lower than that in the central region (first region), but is usually lower. Therefore, the ratio of the abundance ratio in the third region to that in the first region (by mass) may be selected from a range of, for example, about third region / first region (by mass) = 1 / 1.1 to 1 / 20 (e.g., 1 / 1.2 to 1 / 15), preferably about 1 / 1.3 to 1 / 10 (e.g., 1 / 1.5 to 1 / 8), and more preferably about 1 / 2 to 1 / 7 (e.g., 1 / 3 to 1 / 6, preferably 1 / 3.5 to 1 / 5.5). The ratio of the abundance ratio in the second region to the abundance ratio in the first region can be selected, for example, from a range of about second region / first region (mass basis) = 1 / 0.1 to 1 / 5 (e.g., 1 / 0.5 to 1 / 4), and may be, for example, about 1 / 0.8 to 1 / 3 (e.g., 1 / 1 to 1 / 2.5), preferably about 1 / 1.1 to 1 / 2 (e.g., 1 / 1.2 to 1 / 1.8).

[0106] In addition, when measuring by SEM-EDX, the abundance ratio may be the abundance ratio of one element selected from the dielectric filler constituent elements, or may be the ratio of the abundance ratio of one element selected from the dielectric filler constituent elements to the total abundance ratio of all elements constituting the dielectric filler and carbon constituting the resin. In addition, the method of preparing the analysis sample to be subjected to elemental analysis is not particularly limited as long as it does not affect the measurement result of the abundance ratio, and may be prepared by a conventional method, for example, a method of cutting the molded body to extract the cross section (or observation surface), embedding it in a specific resin, and precision polishing, and further, depending on the analysis method, an element not contained in the resin and the dielectric filler may be vapor-deposited on the observation surface.

[0107] In addition, in the above explanation, a method for confirming the non-uniformity of the presence ratio (concentration) of the dielectric filler by elemental analysis was described, but instead of elemental analysis, a method capable of detecting (or confirming) the concentration of the filler, such as a method for analyzing the chemical species, may be used.

[0108] In addition, although the region in the cross section is described in Fig. 2, if the molded body has an aggregated portion in which the dielectric filler penetrates or is exposed on the surface, instead of the cross section, a region may be set in the same manner on the surface of the molded body, and the abundance ratio of the dielectric filler constituent elements may be compared. Usually, the region is set on the cross section, and the cross section may be any cross section, but a cross section (longitudinal cross section) that is approximately parallel to the thickness direction is preferable.

[0109] The central portion of the aggregation portion can be appropriately determined depending on the shape of the aggregation portion. In relation to the manufacturing method (aggregation step) described later, the aggregation portion is usually formed extending in the thickness direction or in a direction forming a predetermined angle with the thickness direction (preferably in the thickness direction). Therefore, the central portion may be a central axis (or central plane) that passes through the center of the aggregation portion (or aggregation portion element) in the cross section (cross section perpendicular to the thickness direction) of the molded body [the center of gravity of the cross-sectional shape of the aggregation portion or the center in the width direction (if linear)] and extends along the direction in which the aggregation portion extends (or the thickness direction).

[0110] The cross-sectional shape of the aggregation portion (or aggregation portion element) in the transverse section is not particularly limited, and may be a shape corresponding to the shape of the aggregation portion described below, for example, approximately circular, approximately elliptical, polygonal (triangular, square, rectangular, etc.), linear (straight or curved), spiral, irregular, etc.

[0111] In the present specification and claims, when the aggregation part is formed by a plurality of aggregation part elements having the same or different shapes and / or directions [for example, when a plurality of aggregation part elements form an aggregation part having a complex (or irregular) shape (for example, a lattice shape, etc.)], the center of the aggregation part of the complex shape can be the center of at least one aggregation part element selected from the aggregation part elements [the center of gravity of the cross-sectional shape of the aggregation part element or the center in the width direction (if linear)]. The cross-sectional shape of the aggregation part element is often relatively simple (for example, the cross-sectional shape exemplified above), and the specific shape of the aggregation part element may be, for example, a dot shape [a polygonal column shape such as a cylinder shape, a square column shape (or a rectangular parallelepiped shape)], a line shape (a wall shape extending linearly or curvedly), etc.

[0112] Representative examples of the complex-shaped agglomeration portions include a cross-sectional U-shaped agglomeration portion (e.g., an agglomeration portion formed by a pair of opposing rectangular parallelepiped elements (or linear elements of a predetermined length) and a rectangular parallelepiped element connected to one end of each of the elements and extending in the direction in which the pair of rectangular parallelepiped elements face each other); a dumbbell-shaped cross-sectional agglomeration portion (e.g., an agglomeration portion formed by a rectangular parallelepiped element and a pair of cylindrical elements connected to both ends of the element); a frame-shaped agglomeration portion (e.g., an agglomeration portion in which a predetermined area such as a triangular frame-shaped agglomeration portion or a rectangular frame-shaped agglomeration portion is partitioned by wall-shaped agglomeration portion elements); a lattice-shaped agglomeration portion (e.g., an agglomeration portion formed by a plurality of first linear elements extending parallel to each other at a predetermined interval and a plurality of second linear elements intersecting the plurality of first linear elements at a predetermined angle and extending parallel to each other at a predetermined interval; a honeycomb-shaped or mesh-shaped agglomeration portion, etc.).

[0113] Since the dielectric filler is aggregated in the aggregation portion, the aggregation portion functions as a region that expresses the function of the dielectric filler in the molded body. Therefore, in the molded body, the aggregation portion is formed into various shapes and structures depending on the application and purpose, but in the present disclosure, even complex shapes and structures can be easily formed by a simple method of applying activation energy to a part of the region.

[0114] The shape of the agglomeration part is not particularly limited, and may be, for example, linear, columnar (or rod-like), spherical, ellipsoidal, irregular, planar, etc. The shape of the agglomeration part may be a shape that combines the above shapes (for example, a lattice shape, etc.), or a shape that corresponds to the above cross-sectional shape. Among these shapes, a linear shape, a columnar shape (cylindrical, rectangular, etc.), a planar shape, a lattice shape, or a shape that combines these shapes is often used.

[0115] The shape of the aggregate portion can be selected from the above shapes, but may be formed in a pattern (pattern or pattern shape) because it is highly productive and can improve the mechanical properties of the molded product due to symmetry and homogeneity. The pattern shape may be one aggregate portion (a continuous single aggregate portion), or usually, a plurality of aggregate portions separated from each other are often formed. The pattern may be, for example, a design (such as a geometric pattern), a pattern, a symbol (or mark), a character, a picture, or a combination of two or more of these, and such a pattern shape may impart design to the molded product. Representative patterns may usually be patterns on the plane of the film-shaped molded product, and examples of such patterns include dots arranged regularly or irregularly, straight or curved lines (lines) arranged in parallel or non-parallel at predetermined intervals (for example, equal intervals, mutually different intervals, etc.), lattice, grid, frame, spiral, and combinations of two or more of these. The shape of the regularly or irregularly arranged dot-like aggregation portions (or the shape of a cross section perpendicular to the thickness direction) may be a polygonal shape such as a square, a circle, a star, an irregular shape, or a combination of two or more of these.

[0116] The molded body of the present disclosure may have a single continuous aggregate portion (for example, an aggregate portion forming a lattice pattern, etc.) or may have a plurality of aggregate portions separated from each other. Of these, it is preferable to have a plurality of aggregate portions from the viewpoint of easily imparting anisotropy to the function of the aggregate portion and reducing the proportion of the dielectric filler to improve the mechanical properties of the molded body. When the molded body has a plurality of aggregate portions, the shapes of the aggregate portions may be the same or different. In the present disclosure, by combining masks of various shapes corresponding to the region to which active energy is applied (polymerization region or curing region) with a three-dimensional mold for molding a resin into a predetermined shape, aggregate portions of various shapes can be easily formed, and molded bodies having different shapes of aggregate portions can also be easily formed. From the viewpoint of productivity, etc., a molded body having aggregate portions with approximately the same shape is preferable. In particular, it may be a film-shaped molded body (particularly a dielectric film or sheet) in which a plurality of aggregate portions form a pattern shape and at least one of the plurality of aggregate portions extends in the thickness direction and crosses (or penetrates) the thickness direction. The aggregation portions (both ends in the thickness direction) may be exposed on the surface (particularly, both the front and back surfaces) of the sheet-like molded product.

[0117] The size of the aggregation part, such as the width or diameter (or the minimum width of the shape of the aggregation part as viewed in the thickness direction), is not particularly limited and may be, for example, 1 mm or more, but in the present disclosure, aggregation parts of relatively small sizes (for example, about 1 mm or less) can be formed. Therefore, the size of the aggregation part can be selected from the range of about 0.01 to 500 μm (for example, 0.1 to 300 μm), and may be, for example, 1 to 200 μm or less, preferably about 10 to 150 μm.

[0118] The molded article of the present disclosure may be in the form of a one-dimensional (e.g., fibrous), two-dimensional (e.g., plate, sheet, film, etc.), or three-dimensional molded article. Of these, the two-dimensional shape is often used.

[0119] The thickness (average thickness) of the two-dimensional molded body can be selected, for example, from a range of about 0.1 μm to 1 mm, and may be, for example, about 0.5 to 500 μm (for example, 1 to 100 μm), preferably about 3 to 80 μm (for example, 5 to 50 μm), and more preferably about 8 to 45 μm (for example, 10 to 40 μm). In particular, when forming a free-standing film, it may be, for example, 5 μm or more (for example, 10 to 100 μm), preferably 20 μm or more (for example, 25 to 70 μm), and more preferably about 30 to 50 μm.

[0120] [Method of manufacturing molded body] The manufacturing method of the molded body of the present disclosure includes an aggregation step in which active energy is applied to a portion of a liquid precursor containing a resin precursor and a dielectric filler to aggregate the dielectric filler. In the aggregation step, the active energy is applied to a portion of the region, whereby the resin precursor is polymerized, and the dielectric filler that was uniformly dispersed inside the molded body moves and aggregates in a portion of the liquid precursor. The portion of the region where the dielectric filler aggregates is either a region to which active energy is not applied (unpolymerized region or unexposed region) or a region to which active energy is applied (polymerized region or exposed region). In the method of the present disclosure, the dielectric filler can be aggregated in either the unpolymerized region or the polymerized region by adjusting the combination of the formulations and the manufacturing conditions (particularly, the types of resin and dielectric filler to be combined). Therefore, once the desired aggregation morphology is determined, the desired pattern can be easily formed by first confirming the conditions or combinations that will cause the dielectric filler to move to either the unpolymerized region or the polymerized region by applying activation energy, and then applying activation energy to a region other than the region corresponding to the desired aggregation morphology if the dielectric filler will move to the unpolymerized region, or conversely, applying activation energy to the region corresponding to the desired aggregation morphology if the dielectric filler will move to the polymerized region.

[0121] In this disclosure, the detailed mechanism by which the dielectric filler behaves in this manner is unclear, but it can be assumed that this is because, as the resin precursor polymerizes to produce resin in the area to which activation energy is applied, a change occurs in the affinity relationship between the resin components [the resin precursor and its polymer (cured product)] and the dielectric filler.

[0122] In the present disclosure, since the aggregation portion is formed in this manner, it is possible to suppress the occurrence of voids (such as voids occurring at the resin / filler interface) that are often seen in resin molded bodies containing fillers. In addition, when the dielectric filler is aggregated in the polymerization region, the thickness of the aggregation portion may be larger than the thickness of the non-aggregation portion.

[0123] In the aggregation step, the resin precursor can be selected depending on the type of resin. When the resin is a thermoplastic resin, it may contain a monomer (monofunctional polymerizable compound) for forming a thermoplastic resin as a polymerizable compound. When the resin is a cured product of a curable resin (such as a cured product having a three-dimensional mesh structure), it may contain a polyfunctional polymerizable compound.

[0124] The liquid precursor may not contain a solvent (or a dispersion medium), or may further contain a solvent to reduce the viscosity of the liquid precursor, in addition to the cationically polymerizable compound and the filler (and other additives as necessary).

[0125] Examples of the solvent (or dispersion medium) include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (acetic acid esters such as methyl acetate, ethyl acetate, n-butyl acetate, etc.), water, alcohols (ethanol, isopropanol, butanol, cyclohexane, etc.), and the like. Examples of the solvent include cyclohexanol, cellosolves [methyl cellosolve, ethyl cellosolve, propylene glycol monomethyl ether (1-methoxy-2-propanol), cellosolve acetates, sulfoxides (dimethyl sulfoxide), amides (dimethylformamide, dimethylacetamide), carbonates [for example, linear carbonates such as dimethyl carbonate and diethyl carbonate, cyclic carbonates such as ethylene carbonate and propylene carbonate (or propylene carbonate)], etc. The solvent may be a mixed solvent. Among these solvents, alcohols such as 2-propanol, carbonates such as propylene carbonate, esters such as n-butyl acetate, etc. are often used.

[0126] The viscosity of the solvent at 20°C may be, for example, about 0.5 to 100 mPa·s (e.g., 0.6 to 50 mPa·s), preferably about 0.5 to 20 mPa·s (e.g., 0.7 to 10 mPa·s), and more preferably about 0.5 to 5 mPa·s (e.g., 1 to 3 mPa·s). The viscosity can be measured using a conventional viscometer (such as a single-cylinder rotational viscometer). If the viscosity of the solvent is too high, there is a risk that the viscosity of the liquid precursor cannot be sufficiently reduced.

[0127] When a solvent is contained, the proportion thereof is, for example, 300 parts by mass or less (e.g., 1 to 200 parts by mass), preferably 180 parts by mass or less (e.g., 50 to 150 parts by mass), and preferably 130 parts by mass or less (e.g., 80 to 120 parts by mass) relative to 100 parts by mass of the liquid precursor. If the amount of the solvent is too small, there is a risk that the viscosity of the liquid precursor cannot be sufficiently reduced, and if it is too large, there is a risk that it becomes difficult to prepare a molded body with a large thickness.

[0128] The liquid precursor for imparting the active energy may be filled into a mold depending on the desired shape, or may be applied to a sheet or film-shaped molded product. Examples of application methods include conventional methods such as roll coater, air knife coater, blade coater, rod coater, reverse coater, bar coater, comma coater, dip / squeeze coater, die coater, gravure coater, microgravure coater, silk screen coater method, dip method, spray method, spinner method, etc.

[0129] Examples of the active energy include thermal energy from a laser or the like, and active rays such as ultraviolet rays and electron beams. Of these, active rays such as ultraviolet rays and electron beams are preferred, and ultraviolet rays are particularly preferred from the standpoint of handling and the like.

[0130] The method of applying active energy can select an energy source (heat source or light source) depending on the type of active energy. When the active energy is ultraviolet light, for example, a deep UV lamp, a low pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a halogen lamp, a laser light source (a light source such as a helium-cadmium laser or an excimer laser) can be used as the light source.

[0131] When ultraviolet light is used as the actinic ray (light energy), the illuminance may be appropriately selected depending on the type and concentration of the polymerizable compound. The illuminance at a wavelength of 365 nm is, for example, 0.1 to 20 mW / cm. 2 (For example, 1 to 18 mW / cm 2 ), preferably 0.3 to 15 mW / cm 2(For example, 5 to 12 mW / cm 2 ), more preferably 0.6 to 10 mW / cm 2 (For example, 6 to 9.5 mW / cm 2 The irradiation time may be selected depending on the illuminance, and may be, for example, about 1 to 60 minutes, preferably 3 to 25 minutes, and more preferably about 5 to 15 minutes.

[0132] In the aggregation step, polymerization of the resin precursor in the applied region can be initiated by applying active energy to a partial region of the liquid precursor, and the dielectric filler can be moved to a region to which the active energy is not applied or to a region to which the active energy is applied, thereby forming an aggregated portion and a non-aggregated portion. In this step, polymerization of the resin precursor may be completed, or polymerization may be completed in a polymerization step described later.

[0133] The method of applying active energy to a portion of a liquid precursor (or an A-stage precursor) can be appropriately selected depending on the type of active energy. For example, in the case of thermal energy, a portion of the region may be irradiated with laser light or the like. In the case of active light rays such as ultraviolet light or electron beams, a photomask having an area capable of blocking the active light rays from reaching the uncured regions (or unpolymerized regions) may be used to irradiate a portion of the region (cured regions or polymerized regions) with the active light.

[0134] When forming a sheet-shaped molded product, in the aggregation step, active energy may be applied (or irradiated) in an oblique direction at a predetermined angle to a planar liquid precursor such as a coating film, but it is usually preferable to irradiate the planar liquid precursor in a direction approximately perpendicular to the surface. By irradiating approximately perpendicularly, the dielectric filler is aggregated or oriented (regularly or randomly oriented) in the thickness direction of the sheet-shaped molded product, and aggregated parts are easily formed that extend in the thickness direction (irradiation direction) and have a form in which the dielectric filler crosses or penetrates (or a form in which the dielectric filler is exposed on the surface).

[0135] In addition to the aggregation step, the method for producing a molded body of the present disclosure preferably further includes a polymerization completion step of applying active energy to a region (uncured region or unpolymerized region) of the precursor molded body (semi-solid precursor molded body or solid precursor molded body, or B-stage precursor molded body) that has been subjected to the aggregation step, to which active energy has not been applied, to complete polymerization. By passing through the polymerization completion step, the resin precursor in the region to which active energy has not been applied can also be polymerized to form a resin.

[0136] In the polymerization completion step, the region to which activation energy is applied may be any region including the region to which activation energy was not applied in the aggregation step. However, a method of applying activation energy to the entire region is preferred, since it is easy to operate, has excellent productivity, and allows the polymerization to proceed further to improve the mechanical properties of the molded body.

[0137] The activation energy may be the same as that in the aggregation step, or the conditions for applying the activation energy may be changed to be stronger. Also, the illuminance may be increased stepwise. When using activation light (light energy), if the irradiation time is too long, the productivity may decrease.

[0138] In the case where the resin is a cationic polymerizable compound, the polymerization may be completed in the polymerization completion step by applying thermal energy (or annealing treatment) to utilize a dark reaction (post-polymerization) of the cationic polymerizable compound. The annealing temperature may be, for example, 50 to 200°C (e.g., 70 to 180°C), preferably 80 to 150°C (e.g., 90 to 130°C), and more preferably about 100 to 120°C. The heating time may be, for example, 10 to 120 minutes, and preferably about 30 to 60 minutes.

[0139] In the present disclosure, a bonded body (composite molded body) in which the substrate and the molded body are bonded may be formed by molding the molded body while the liquid precursor is brought into contact with a predetermined substrate by a method such as coating.

[0140] The material of the substrate is not particularly limited, and may be either an organic material or an inorganic material.

[0141] Examples of organic materials include resins [e.g., olefin-based resins such as polyethylene and polypropylene, styrene-based resins such as ABS resin, vinyl-based resins such as polyvinyl chloride resin, (meth)acrylic resins such as polymethyl methacrylate, polyester-based resins such as polyethylene terephthalate (PET), polycarbonate-based resins, polyamide-based resins, polyimide-based resins, cellulose derivatives such as cellulose esters and cellulose ethers, thermoplastic elastomers, etc.]; synthetic rubber materials (isoprene rubber, butyl rubber, etc.); resin or rubber foams (e.g., polyurethane foam, polychloroprene rubber foam, etc.); materials derived from plants or animals (wood, pulp, natural rubber, leather, wool, etc.), etc.

[0142] Examples of inorganic materials include ceramics (glass, silicon, cement, etc.); metals (e.g., elemental metals (aluminum, iron, nickel, copper, zinc, chromium, titanium, etc.), alloys containing these metals (aluminum alloys, steel (stainless steel, etc.), etc.)), etc.).

[0143] Of these materials, resins (for example, polyester resins, polyimide resins, etc., preferably polyimide resins, etc.), ceramics (glass, etc.), and metals (copper, etc.) are often used.

[0144] The form (shape) of the substrate is not particularly limited, and examples thereof include one-dimensional shapes such as fiber (thread, rope, wire, etc.), two-dimensional shapes such as plate, sheet, film, foil, cloth or cross (woven fabric, knitted fabric, nonwoven fabric, etc.), and paper (high-quality paper, glassine paper, craft paper, Japanese paper, etc.), and three-dimensional shapes such as lump, block, rod (cylinder, polygonal column, etc.), and tube.

[0145] Among these forms, they are often two-dimensional, such as plates, sheets, films, and foils.

[0146] It should be noted that each feature disclosed herein may be combined with any other feature disclosed herein. EXAMPLES

[0147] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The raw materials used are as follows, and the obtained laminates were evaluated by the following methods.

[0148] [Raw materials] (cationically polymerizable compound) NPG: Neopentyl glycol diglycidyl ether, "Epogosey (registered trademark) NPG (D)" manufactured by Yokkaichi Chemical Co., Ltd., viscosity 8 mPa·s (25°C, catalog value) EP1: CEL2021P: 3,4-epoxycyclohexylmethyl (3,4-epoxy) cyclohexane carboxylate, "Celloxide 2021P" manufactured by Daicel Corporation, viscosity 240 mPa·s (25°C) EP2: (3,4,3',4'-diepoxy)bicyclohexyl, viscosity 60 mPa·s (25°C) (Dielectric filler) BaTiO 3 Barium titanate particles, manufactured by Kanto Chemical Co., Ltd., particle size approx. 100 nm (Initiator) CPI-100P: photocationic polymerization initiator, "CPI (registered trademark)-100P" manufactured by San-Apro Ltd.

[0149] [Tools and equipment used] (base material) Untreated glass: 1mm thick, "S9112" manufactured by Matsunami Glass Co., Ltd.

[0150] (mask) The following photomasks (No. 1 to 7) having the pattern shapes shown in Figures 3 and 4 No.1: Square or square dot photomask with square light-shielding areas of 250μm x 250μm size regularly arranged vertically and horizontally at 250μm intervals (5-inch glass mask manufactured by Tokyo Process Services Co., Ltd.) No. 2: Square or square dot photomask with 50 μm x 50 μm square light-shielding areas regularly arranged vertically and horizontally at 150 μm intervals (Tokyo Process Services Co., Ltd. 5-inch glass mask) No. 3: Square or square dot photomask with 100 μm x 100 μm square light-shielding areas regularly arranged vertically and horizontally at 100 μm intervals (Tokyo Process Services Co., Ltd. 5-inch glass mask) No. 4: Square or square dot photomask with 50 μm x 50 μm square light-shielding areas regularly arranged vertically and horizontally at 50 μm intervals (Tokyo Process Services Co., Ltd. 5-inch glass mask) No. 5: Line or line and space (L / S) photomask with 100 μm wide linear light-shielding areas regularly arranged at 100 μm intervals (Tokyo Process Services Co., Ltd. 5-inch glass mask) No. 6: A photomask with a lattice pattern, 100 μm x 100 μm square transparent areas regularly arranged vertically and horizontally at 100 μm intervals (5-inch glass mask manufactured by Tokyo Process Services Co., Ltd.) No. 7: Square or square dot photomask (5-inch glass mask manufactured by Tokyo Process Services Co., Ltd.) in which square light-shielding areas of 100 μm x 100 μm size are regularly arranged in a checkerboard pattern.

[0151] (Device) Bar coater: Daiichi Rika Co., Ltd. 8φ×300mm Spot UV device: Hamamatsu Photonics "LC8" Digital microscope: Hirox Corporation "KH-8700"

[0152] [Evaluation method] (curable) The curability of the obtained film was evaluated according to the following criteria.

[0153] ○…Fully cured after UV irradiation (2nd or 3rd stage) △…Not completely cured after UV irradiation (2nd or 3rd stage), fully cured after annealing ×: Not completely hardened even after annealing.

[0154] (Filler controllability) Based on the CCD images observed by a digital microscope, the controllability of the dielectric filler in the obtained film was relatively evaluated according to the following criteria.

[0155] ◎…Low amount of filler remaining in non-aggregated areas ○…Medium amount of filler remaining in non-aggregated areas △: Large amount of filler remaining in non-aggregated areas ×: No transfer of mask pattern.

[0156] (Dielectric constant) As a pretreatment step, platinum was evaporated in a circle shape with a diameter of 40 mm on both sides of the film to be measured for dielectric constant, so that the centers were aligned, using an ion sputtering device ("MC1000" manufactured by Hitachi High-Tech Corporation). The dielectric constant (relative dielectric constant) of the pretreated film was measured under the following conditions, and the relative value to the corresponding comparative example was taken as the degree of increase. Standards: Compliant with JIS C2138 Dielectric constant measuring device: Cencept42 (Novocontrol Technologies) Temperature and humidity: 23℃, 50%RH Electrode shape: Circular electrode (diameter 40 mm) without guard ring Electrode placement: The center of the test piece is aligned with the center of the electrode. Test voltage: 1.0V Test frequency: 10Hz~1MHz. (Flexibility) The obtained film having the coating layer was wrapped around a glass rod having a diameter of 5 mm to evaluate flexibility, and films that did not break were rated as "good".

[0157] [Comparative Examples 1 to 2] The components were mixed and stirred in the ratios shown in Table 1 to prepare a liquid precursor containing a cationic polymerizable compound, a dielectric filler, and an initiator. The prepared liquid precursor was applied to a glass substrate using a bar coater to form a coating film. The obtained coating film was irradiated with ultraviolet light (wavelength 365 nm) using a spot UV device under the conditions (illuminance, irradiation time) shown in Table 1 without using a mask, and then the illuminance was increased and ultraviolet light was irradiated without using a mask to prepare a film having a coating layer with a thickness shown in Table 1.

[0158] [Examples 1 to 4] The components were mixed and stirred in the ratios shown in Table 1 to prepare a liquid precursor containing a cationic polymerizable compound, a dielectric filler, and an initiator. The prepared liquid precursor was applied to a glass substrate using a bar coater to form a coating film. The obtained coating film was irradiated with ultraviolet light (wavelength 365 nm) through a mask using a spot UV device under the conditions (illuminance, irradiation time) shown in Table 1 (first step), and then quickly irradiated with ultraviolet light without a mask (second step), to prepare a film having a coating layer with a thickness shown in Table 1.

[0159] [Examples 5 to 18] The components were mixed and stirred in the ratios shown in Table 1 to prepare a liquid precursor containing a cationic polymerizable compound, a dielectric filler, and an initiator. The prepared liquid precursor was applied to a glass substrate using a bar coater to form a coating film. The obtained coating film was irradiated with ultraviolet light (wavelength 365 nm) through a mask using a spot UV device under the conditions (illuminance, irradiation time) shown in Table 1 (first stage), then quickly irradiated with ultraviolet light without a mask (second stage), and further irradiated with ultraviolet light without a mask at an increased illuminance (third stage), to prepare a film having a coating layer with a thickness shown in Table 1.

[0160] The evaluation results of the films obtained in Comparative Examples 1 and 2 and Examples 1 to 18 are shown in Table 1.

[0161] CCD photographs of the obtained films are shown in Figures 5 to 24. In the surface observation images, the filler aggregated parts are shown in black (dark color) because the observation was performed using transmitted light.

[0162] [Table 1]

[0163] As is clear from the results in Table 1, the films of the examples had excellent curability and the dielectric filler was well controlled.

[0164] [Comparative Example 3] The components were mixed and stirred in the ratios shown in Table 2 to prepare a liquid precursor containing a cationic polymerizable compound and an initiator. The prepared liquid precursor was applied to a glass substrate using a bar coater to form a coating film. The obtained coating film was irradiated with ultraviolet light (wavelength 365 nm) using a spot UV device under the conditions (illuminance, irradiation time) shown in Table 2 without using a mask, to prepare a film having a coating layer with a thickness shown in Table 2.

[0165] [Comparative Examples 4 to 7] The components were mixed and stirred in the ratios shown in Table 2 to prepare a liquid precursor containing a cationic polymerizable compound, a dielectric filler, and an initiator. The prepared liquid precursor was applied to a glass substrate using a bar coater to form a coating film. The obtained coating film was irradiated with ultraviolet light (wavelength 365 nm) using a spot UV device under the conditions (illuminance, irradiation time) shown in Table 2 without using a mask, and then the illuminance was increased and ultraviolet light was irradiated without using a mask to prepare a film having a coating layer with a thickness shown in Table 2.

[0166] [Examples 19 to 29] The components were mixed and stirred in the ratios shown in Table 2 to prepare a liquid precursor containing a cationic polymerizable compound, a dielectric filler, and an initiator. The prepared liquid precursor was applied to a glass substrate using a bar coater to form a coating film. The obtained coating film was irradiated with ultraviolet light (wavelength 365 nm) through a mask using a spot UV device under the conditions (illuminance, irradiation time) shown in Table 2 (first stage), then quickly irradiated with ultraviolet light without a mask (second stage), and further irradiated with ultraviolet light without a mask at an increased illuminance (third stage) to prepare a film having a coating layer with a thickness shown in Table 2.

[0167] The evaluation results of the films obtained in Comparative Examples 3 to 7 and Examples 19 to 29 are shown in Table 2. CCD photographs of the obtained films are shown in Figures 25 to 39. [Table 2]

[0168] As is clear from the results in Table 2, the films of the Examples had excellent curing properties, the dielectric filler was well controlled, and the dielectric constant was improved. The relative dielectric constant is shown as a value relative to the Comparative Example, and the dielectric constant of the Examples was increased by 20% or more compared to the Comparative Example. Furthermore, the dielectric films obtained in the Examples did not break even when wrapped around a glass rod with a diameter of 5 mm, and had excellent flexibility. [Industrial Applicability]

[0169] The molded article of the present disclosure can be used as a dielectric material in various electric and electronic devices, transportation equipment, etc., and is particularly suitable as a dielectric material used as a passive element component such as a capacitor, resistor, inductor, etc. Among these, the film-shaped molded article is also excellent in flexibility and is therefore suitable as a dielectric film (high dielectric constant insulating film), and is particularly suitable as a film capacitor for home appliances, in-vehicle electronic devices, industrial equipment, power electronics equipment, etc. [Explanation of symbols]

[0170] 1…Agglutination part 1a...Central region (central part, near the center or first region) 1b...Intermediate area (middle part, intermediate area or second area) 1c...Peripheral area (periphery, near the interface, or third area) 2…Non-agglomerated part 3…Interface 4…Center of the agglomeration

Claims

1. Contains a resin and a dielectric filler; The dielectric filler is an inorganic filler formed of a titanium-containing composite metal oxide, A molded body which is formed of an aggregation portion, which is a region where the dielectric filler is aggregated, and a non-aggregation portion, which is a region other than the aggregation portion, and in which the proportion of the dielectric filler in the aggregation portion gradually decreases toward the interface with the non-aggregation portion, at least near the interface.

2. 2. The molded article according to claim 1, wherein the resin is a cured product of a photocurable resin.

3. 3. The molded article according to claim 2, wherein the photocurable resin is a cationic polymerizable compound.

4. The molded article according to any one of claims 1 to 3, wherein the ratio of the dielectric filler is 0.1 to 100 parts by mass per 100 parts by mass of the resin.

5. The molded article according to any one of claims 1 to 4, which is in the form of a film.

6. 6. The molded article according to claim 5, wherein a plurality of agglomeration portions form a pattern shape, and at least one of the plurality of agglomeration portions is formed in a penetrating form extending in the thickness direction.

7. The molded article according to any one of claims 1 to 6, which is a dielectric film.

8. The method for producing a molded body according to any one of claims 1 to 7, comprising: applying active energy to a partial region of a liquid precursor containing a resin precursor and a dielectric filler to aggregate the dielectric filler to obtain a precursor molded body.

9. The method according to claim 8, further comprising a polymerization completion step of applying activation energy to the uncured region of the precursor molded body that has been subjected to the aggregation step to complete the polymerization.

10. 10. The method according to claim 8, wherein the liquid precursor contains a photoacid generator, and the active energy is actinic radiation.

11. A molded article obtained by the method according to any one of claims 8 to 10.

12. A liquid precursor for forming a molded body comprising a photocurable resin and a dielectric filler, the dielectric filler being an inorganic filler formed of a titanium-containing composite metal oxide, the liquid precursor having an aggregate portion which is a region where the dielectric filler is aggregated, and a non-aggregated portion which is a region other than the aggregate portion, the liquid precursor comprising a photocurable resin and a dielectric filler.

13. A bonded body obtained by bonding a substrate made of a resin, ceramic or metal to the molded body according to any one of claims 1 to 7 and 11.

14. 14. The assembly of claim 13 which is a capacitor.

Citation Information

Patent Citations

  • Dispersant for coal-water slurry

    JP1987064897A

  • Resin composition and application thereof

    JP2006104302A

  • Sheetlike composite material and method for producing the same

    JP2007332224A

  • Resin composition, molded body, and resin composition manufacturing method

    JP2016222750A

  • Resin composition

    JP2017014406A